Whale optimisation algorithm-based controller design for reverse osmosis desalination plants. (2019) - Rathore, Natwar Singh; Singh, V.P.
In this contribution, whale optimisation algorithm (WOA)-based controllers are presented for reverse osmosis (RO) desalination plants. Two proportional-integral-derivative (PID) controllers are designed for flux and conductivity of RO plant model. The tuning of these controllers is carried out with a newly proposed algorithm, i.e., WOA. The minimisation of integral-of-squared-error (ISE) is considered as performance index for design of objective function in the problem. The performance of proposed controllers is compared with other optimisation algorithms-based controllers. Simulation results show the supremacy of WOA-based controllers over the other controllers. The proposed controllers are found best for RO desalination plants in terms of control of RO unit model.